1973
DOI: 10.2134/agronj1973.00021962006500050026x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Dry Matter and Nitrogen Content of Burley Tobacco Growing in Fertilizer‐induced Acid Soil1

Abstract: Nicotiana tabarum L. cv. ‘Burley 21’ was grown in the field to determine the influence of rate of N fertilization on accumulation of dry matter and certain nitrogenous constituents during the growing season. Nitrogenous compounds in tobacco are presently of interest from a human health standpoint and the chemical constituents of tobacco leaves are known to be associated with dry matter accumulation. Accumulation of dry matter, protein N, and total N in plants treated with high rates of N fertilizer (up to 450 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 3 publications
(5 reference statements)
4
20
0
Order By: Relevance
“…Although substantially greater decreases due to NH4 have been frequently reported (30), such factors as level of fertilization, source of N, plant species utilized, and soil buffering capacity all may influence the extent to which N form affects soil pH. The pH decreases in this experiment are similar to those recorded by Sims and Atkinson (31,32) and Reneau and co-workers (29). For treatments receiving NO3-N, a measurable increase in pH occurred only at initial pH of 6 In Experiment 2, application of NH4 to the soil also resulted in soil pH decreases (Table 4) of 0.3 to 0.4 pH units (initial pH 6.8).…”
Section: Analytical Proceduressupporting
confidence: 83%
“…Although substantially greater decreases due to NH4 have been frequently reported (30), such factors as level of fertilization, source of N, plant species utilized, and soil buffering capacity all may influence the extent to which N form affects soil pH. The pH decreases in this experiment are similar to those recorded by Sims and Atkinson (31,32) and Reneau and co-workers (29). For treatments receiving NO3-N, a measurable increase in pH occurred only at initial pH of 6 In Experiment 2, application of NH4 to the soil also resulted in soil pH decreases (Table 4) of 0.3 to 0.4 pH units (initial pH 6.8).…”
Section: Analytical Proceduressupporting
confidence: 83%
“…In the current study, it is not known whether the higher nutrient concentrations due to Ca are the result of higher influx rates of nutrients into root cells or to lower efflux rates. In burley tobacco culture, soluble Ca most likely lessens or prevents K efflux, since soil pH often is lowered markedly by fertilizer induced soil acidity (3,4,5). Also, Ca may partially negate any inhibitory effects of the higher concentrations of H in the soil environment on K uptake by plant roots.…”
Section: Discussionmentioning
confidence: 99%
“…The large amounts of fertilizers commonly applied in burley tobacco (Nicotiana tabacum L.) production results in lowering the pH of silt loam soils 0.5 to 1.0 unit for much of the growing season (3,4). Hence, initial soil pH needs to be near 6.6 in order to maintain pH at midseason in the range of 5.6 to 6.2, principally to control Mn toxicity, Mo deficiency, and to enhance overall nutrient availability (5,6,7,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported for flue-cured tobacco by Gopalachari et al {6). In similar studies with Burley tobacco, nitrogen concentration decreased significandy from the 6th to the 12th week after transplanting (12), or tended to decrease very litde from the 4th to 10th week after transp~anting and remained constant thereafter (7). The lower leaf nitrogen concentration in Oriental tobacco at harvesting time compared to that of the previous growth stages is in agreement with diminished nitrogen uptake during harvesting in the other tobacco classes.…”
Section: Weeks After Transplantingmentioning
confidence: 93%
“…Also the nitrogen form affects .the growth and concentration of nitrogen, phosphorus, potassium, calcium and magnesium in tobacco plants (13). Dry matter and nutrient accumulation in plant tissue studies with flue-cured, Burley, Maryland and wrapper tobacco have been reported on (1,2,5,6,7,10,11,12). Concentrations of plant nutrients in various plant parts have been studied in other crops (5).…”
Section: Introductionmentioning
confidence: 99%